Creative Remembering--and Prudent Forgetting--on Our Way to Christian Unity - Henry, Patrick (Journal of ecumenical studies, 2017)
The distance from Pope Pius XI's Mortalium animos in 1928, forbidding Catholic participation in gatherings of non-Catholics, to the Joint Declaration on Justification signed by the Vatican and the Lutheran World Federation in 1999, beggars measurement. The landscape had to change, and it was a whole range of creative rememberings and prudent forgettings that altered the lay of the theological and ecclesial land. We need to be alert to the way memory works; its shape-shifting is influenced by serendipity, art, academic fashion, the counter-intuitive, chronological snobbery (and regret), and research itself. Denominational bones ache, while ecumenical hearts are strangely warmed.